2007
DOI: 10.1140/epjc/s10052-007-0229-3
|View full text |Cite
|
Sign up to set email alerts
|

The extraction of the nuclear sea-quark distribution and energy loss effect in a Drell–Yan experiment

Abstract: The next-to-leading order and leading order analysis are performed on the differential cross section ratio from Drell-Yan process. It is found that the effect of next-to-leading order corrections can be negligible on the differential cross section ratios as a function of the quark momentum fraction in the beam proton and the target nuclei for the current Fermilab and future lower beam proton energy. The nuclear Drell-Yan reaction is an ideal tool to study the energy loss of the fast quark moving through cold n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…The available nuclear Drell-Yan data are in the form of ratios over deuterium and beryllium, R A/Be (x 1(2) ) for the Fermilab Experiment866, and R A/D (x 1(2) ) for the Fermilab Experiment772, respectively. The x 1 dependence of cross section rations R A 1 /A 2 (x 1 ) and R A/D (x 2 ) data, which is different from the results with E866 data [18] . In fact, the values of the parameter α (or β) in the quark energy loss expression should be the same for fitting the ratios R A 1 /A 2 (x 1 ) or R A 1 /A 2 (x 2 ) from the nuclear Drell-Yan experiment if the experimental data are sufficiently precise.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…The available nuclear Drell-Yan data are in the form of ratios over deuterium and beryllium, R A/Be (x 1(2) ) for the Fermilab Experiment866, and R A/D (x 1(2) ) for the Fermilab Experiment772, respectively. The x 1 dependence of cross section rations R A 1 /A 2 (x 1 ) and R A/D (x 2 ) data, which is different from the results with E866 data [18] . In fact, the values of the parameter α (or β) in the quark energy loss expression should be the same for fitting the ratios R A 1 /A 2 (x 1 ) or R A 1 /A 2 (x 2 ) from the nuclear Drell-Yan experiment if the experimental data are sufficiently precise.…”
Section: Resultscontrasting
confidence: 82%
“…It is proved that there is quark energy loss effect in nuclear Drell-Yan reactions, which is an ideal tool to study the energy loss of the fast quark moving through cold nuclei. In the recent paper [18] , a next-to-leading order and a leading order analysis are performed of the differential cross section ratios from the proton-induced Drell-Yan reaction off nuclei. It is found that the next-to-leading order corrections can be negligible on the differential cross section ratios for the current Fermilab and future lower proton energy.…”
Section: Introductionmentioning
confidence: 99%
“…We have also studied(not shown here) the dependence of the parameter α used in the expression given in Eq. (27) for energy loss, we have varied α in the range 0.5 < α < 3, corresponding to the range of values used in literature [24,25,44], for…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that the differences between the calculated results for the leading order Drell-Yan ratios and that for the next-to-leading order are very small. The reason may be that the form of the differential cross section ratio as a function of the quark momentum fraction ( ( ) R x x x , , A A F 1 2 1 2 ) avoids the influence of the QCD next-to-leading order correction [31]. We have found that the comparisons with the E906, E866 and NA3 experimental data exhibit a clear disagreement with the corrections alone from the nPDF, especially for the E906 and NA3 measurements at the lower incident energy.…”
Section: Discussionmentioning
confidence: 99%